Partial pancreatoduodenectomy versus duodenum-preserving pancreatic head resection in chronic pancreatitis: the multicentre, randomised, controlled, double-blind ChroPac trial. Issue 10099 (9th September 2017) - Diener, Markus K; Hüttner, Felix J; Kieser, Meinhard; Knebel, Phillip; Dörr-Harim, Colette; Distler, Marius; Grützmann, Robert; Wittel, Uwe A; Schirren, Rebekka; Hau, Hans-Michael; Kleespies, Axel; Heidecke, Claus-Dieter; et al.
Summary: Background: There is substantial uncertainty regarding the optimal surgical treatment for chronic pancreatitis. Short-term outcomes have been found to be better after duodenum-preserving pancreatic head resection (DPPHR) than after partial pancreatoduodenectomy. Therefore, we designed the multicentre ChroPac trial to investigate the long-term outcomes of patients with chronic pancreatitis within 24 months after surgery. Methods: This randomised, controlled, double-blind, parallel-group, superiority trial was done in 18 hospitals across Europe. Patients with chronic pancreatitis who were planned for elective surgical treatment were randomly assigned to DPPHR or partial pancreatoduodenectomy with a central web-based randomisation tool. The primary endpoint was mean quality of life within 24 months after surgery, measured with the physical functioning scale of the European Organisation for Research and Treatment of Cancer QLQ-C30 questionnaire. Primary analysis included all patients who underwent one of the assigned procedures; safety analysis included all patients who underwent surgical intervention (categorised into groups as treated). Patients and outcome assessors were masked to group assignment. The trial was registered, ISRCTN38973832. Recruitment was completed on Sept 3, 2013. Findings: Between Sept 10, 2009, and Sept 3, 2013, 250 patients were randomly assigned to DPPHR (n=125) or partial pancreatoduodenectomy (n=125), of whom 226 patients (115 in the DPPHR group and 111 in the partial pancreatoduodenectomy group) were analysed. No difference in quality of life was seen between the groups within 24 months after surgery (75·3 [SD 16·4] for partial pancreatoduodenectomy vs 73·0 [16·4] for DPPHR; mean difference −2·3, 95% CI −6·6 to 2·0; p=0·284). The incidence and severity of serious adverse events did not differ between the groups. 70 (64%) of 109 patients in the DPPHR group and 61 (52%) of 117 patients in the partial pancreatoduodenectomy group had at least one serious adverse event, with the most common being reoperations (for reasons other than chronic pancreatitis), gastrointestinal problems, and other surgical morbidity. Interpretation: No differences in quality of life after surgery for chronic pancreatitis were seen between the interventions. Results from single-centre trials showing superiority for DPPHR were not confirmed in the multicentre setting. Funding: German Research Foundation (DFG).